The impact of auditor change on the significance of accounting information value relevance, mediated by earnings management practices - Salih, Jalil Ibrahim; Shibli, Abdulhussein Tofeeq (Edelweiss Applied Science and Technology, 2025)
This study seeks to evaluate the impact of Auditor Change (AG) on the appropriateness of the Accounting Information Value Relevance (AIVR) in Iraqi banks listed on the Iraq Stock Exchange, verifying the effects of the Earnings Management Practices (EMPS) by Iraqi banks listed on the Iraq Stock Exchange on the appropriateness of the AIVR. The research sample consisted of 19 Iraqi banks listed on the Iraq Stock Exchange from 2014 to 2022, totaling 171 annual observations. These observations were derived from the banks' financial reports published on the Iraq Stock Exchange website. The researcher utilized the statistical software packages SPSS 28 and STATA 17 for data analysis. The results showed that the independent variable (AG) negatively affects EMPS and positively affects the appropriateness of the AIVR. EMPS also negatively affects the appropriateness of the AIVR. Therefore, EMPS can be an intermediary between the independent variable (AG) and the appropriateness of the AIVR.